Influence of Environmental Fluctuations on Non-Diffracting Beams Used to Secure Data - Kadem, Kamal H.; Mohammed, Mohammed F. (Al-Nahrain Journal for Engineering Sciences, 2025)
This study simulates a free-space optical communication system that uses optical beams with varying responses to atmospheric disturbances to secure transmitted data. Atmospheric turbulence was modeled with high accuracy to replicate real-world conditions closely. Non-diffracting beams were generated and used to represent optical beams and compared in two scenarios, conventional data transmission, and optifusion data protection. This approach facilitated a comprehensive analysis of the transmission environment and the effectiveness of optifusion, identifying the most suitable non-diffracting beam types for secure data propagation. By analyzing the values of key performance metrics of the selected non-diffracting beams across different weather conditions and long propagation distances, the study demonstrated the simulation system’s reliability and the optifusion method’s effectiveness in enhancing data security. The results showed that non-diffracting beams resist atmospheric turbulences strongly, emphasizing their potential for secure, long-range free-space optical communications.